Benign Mass in Tonsil- Cavernous Hemangioma - Joseph, Sumitha (JCDR Research and Publications (P) Limited, 2013)
Cavernous hemangioma is also called as ‘ANGIOMA CAVERNOSUM’ or ‘CAVERNOMA’ as benign lesion of blood vessels. They are similar to strawberry hemangioma but deeply situated. Although most often associated with skin it is also sometimes found in mucous membrane, brain and the viscera. The diagnosis of hemangiomas is mainly based on clinical evaluation . Isolated hemangiomas in the tonsillar tissue is a rare occurance. In this we report had a case of adult tonsillar hemangioma of left side associated with recurrent tonsillitis . He was effectively managed surgically without any complications.